Seneca Philosophus - Wildberger, Jula, 1962-; Colish, Marcia L. (Trends in classics. Supplementary volumes, 2014)
Addressing classicists, philosophers, students, and general readers alike, this volume emphasizes the unity of Seneca's work and his originality as a translator of Stoic ideas in the literary forms of imperial Rome. It features a vitalizing diversity of contributors from different generations, disciplines, and research cultures. Prominent Seneca scholars publishing in other languages are for the first time made accessible to anglophone readers.